“The Chalky Children of Evermore”: Coleridge, Keats, and the Romantic Child in PJ Harvey’s I Inside the Old Year Dying (2023) - McInnes, Andrew (Romanticism on the Net)

(untitled) (Université de Montréal, 2024)
PJ Harvey’s I Inside the Old Year Dying adapts twelve poems from her 2022 novel-in-verse Orlam into music mixing folk horror with rock, electronica, and field recordings. Both texts delight in Dorset dialect, weaving together allusions to the Bible, Shakespeare, Coleridge, Keats, and Elvis into a Gothic tale of childhood’s end, sexual violence, and visionary experience. Coleridge’s “Answer to a Child’s Question,” describing bird song as declarations of love, bifurcates into “A Child’s Question, August,” in which Harvey turns Elvis’s “Love Me Tender” into an ornithological demand, and “A Child’s Question, July,” a stomping folk number staging a confrontation with a phallic devil figure, the Ooser Rod. Keats gives the final song its title, “A Noiseless Noise,” a plea for homecoming rendered uncertain by its haunting lyrics and crunching guitars. These Romantic poets speak to Harvey’s own interest in the natural world and the weirder realm of childhood, which spills over into supernaturalism. This article engages with recent work on rock music and Romanticism, connecting it with a parallel interest in Lacanian psychoanalysis, to explore Harvey’s representation of lack on the album as both threatening ghostly dissolution and offering pathways for creative expression.